Measuring the procyclicality of impairment accounting regimes: A comparison between IFRS 9 and US GAAP - Alejandro Buesa; Javier Población García; Javier Tarancón (European Central Bank (ECB), 2019)
The purpose of this paper is to compare the cyclical behavior of various credit impairment accounting regimes, namely IAS 39, IFRS 9 and US GAAP. We model the impact of credit impairments on the Profit and Loss (P&L) account under all three regimes. Our results suggest that although IFRS 9 is less procyclical than the previous regulation (IAS 39), it is more procyclical than US GAAP because it merely requests to provision the expected loss of one year under Stage 1 (initial category). Instead, since US GAAP prescribes that lifetime expected losses are fully provisioned at inception, the amount of new loans originated is negatively correlated with realized losses. This leads to relatively higher (lower) provisions during the upswing (downswing) phase of the financial cycle. Nevertheless, the lower procyclicality of US GAAP seems to come at cost of a large increase in provisions.
Keywords: G21; G28; K20; 330; Banking system; provisions; regulation; cyclicality